2020
DOI: 10.3389/fendo.2020.00029
|View full text |Cite
|
Sign up to set email alerts
|

Stathmin-2 Mediates Glucagon Secretion From Pancreatic α-Cells

Abstract: Inhibition of glucagon hypersecretion from pancreatic α-cells is an appealing strategy for the treatment of diabetes. Our hypothesis is that proteins that associate with glucagon within alpha cell secretory granules will regulate glucagon secretion, and may provide druggable targets for controlling abnormal glucagon secretion in diabetes. Recently, we identified a dynamic glucagon interactome within the secretory granules of the α cell line, αTC1-6, and showed that select proteins within the interactome could … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…This qualitative study demonstrated the plasticity in the network of proteins interacting with glucagon in response to insulin or GABA under high (25 mM) or low (5.5 mM) glucose. Stathmin-2, a member of the family of neuronal phosphoproteins that associates with the secretory pathway in neurons, was identified as a candidate protein for the regulation of glucagon secretion and subsequently shown to modulate glucagon secretion through the lysosomal pathway (140) and may be down-regulated in diabetes in humans (141) and in mice (142). Therefore, disruptions in the routing of glucagon through the lysosomal pathway may contribute to the hyperglucagonemia of diabetes (Figure 4).…”
Section: Novel Proteins In the Regulation Of Glucagon Trafficking And Secretionmentioning
confidence: 99%
“…This qualitative study demonstrated the plasticity in the network of proteins interacting with glucagon in response to insulin or GABA under high (25 mM) or low (5.5 mM) glucose. Stathmin-2, a member of the family of neuronal phosphoproteins that associates with the secretory pathway in neurons, was identified as a candidate protein for the regulation of glucagon secretion and subsequently shown to modulate glucagon secretion through the lysosomal pathway (140) and may be down-regulated in diabetes in humans (141) and in mice (142). Therefore, disruptions in the routing of glucagon through the lysosomal pathway may contribute to the hyperglucagonemia of diabetes (Figure 4).…”
Section: Novel Proteins In the Regulation Of Glucagon Trafficking And Secretionmentioning
confidence: 99%
“…Thus, it is possible that these or other specific proteins present in the secretory granules may be critical to determine the fate of glucagon release vs. lysosomal shuttling. In this regard, a recent study identified stathmin-2, which is present in the membrane of glucagon-containing secretory granules, as a critical protein that diverted glucagon towards endosomal–lysosomal pathways for degradation [ 30 ]. Further studies linking MTORC1 inhibition to the regulation of secretory granule sorting through RAB7 and SNARE family proteins and their potential interaction with lysosomes need to be investigated in the regulation of glucagon crinophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Acquisition of high-resolution images was done by selecting Nyquist XY scan area, 1024 × 1024-pixel size scanning of the selected area and 2D-Deconvolution of the captured images, as we have done previously. 18 .…”
Section: Methodsmentioning
confidence: 99%
“…Colocalization of pixels from each pseudocolored image was used to calculate Pearson’s correlation coefficient (PCC), as we have done previously. 17 , 18 , 22 Regions of interest (ROIs) were manually drawn around each islet and then defined PCC values for colocalization between Stmn2 and target markers (glucagon, insulin, Lamp2A, Rab7, Rab11A, Rab11B) were calculated using the colocalization algorithm of NIS-Elements software. To show the relationships between expression levels of Stmn2 and the target markers (glucagon, insulin, Lamp2A, Rab7, Rab11A, Rab11B) in α or β- cells of the pancreatic islet, binary images were generated using M-Threshold algorithm of NIS-Elements software.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation